2008
DOI: 10.1124/jpet.107.134221
|View full text |Cite
|
Sign up to set email alerts
|

Cyclooxygenase-2-Linked Attenuation of Hypoxia-Induced Pulmonary Hypertension and Intravascular Thrombosis

Abstract: Exogenous prostacyclin is effective in reducing pulmonary vascular resistance in some forms of human pulmonary hypertension (PH). To explore whether endogenous prostaglandins played a similar role in pulmonary hypertension, we examined the effect of deleting cyclooxygenase (COX)-gene isoforms in a chronic hypoxia model of PH. Pulmonary hypertension, examined by direct measurement of right ventricular end systolic pressure (RVESP), right ventricular hypertrophy (n ϭ 8), and hematocrit (n ϭ 3), was induced by 3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 39 publications
0
30
0
Order By: Relevance
“…COX-2 expression is increased in lung tissues from PAH patients and in PAs from hypoxia-induced PAH mouse models (4,5). As such, we also observed the substantial induction of all PG products, including PGE 2 (Supplemental Figure 1; supplemental material available online with this article; doi:10.1172/JCI77656DS1) in lungs in response to chronic hypoxia.…”
Section: Resultsmentioning
confidence: 52%
See 1 more Smart Citation
“…COX-2 expression is increased in lung tissues from PAH patients and in PAs from hypoxia-induced PAH mouse models (4,5). As such, we also observed the substantial induction of all PG products, including PGE 2 (Supplemental Figure 1; supplemental material available online with this article; doi:10.1172/JCI77656DS1) in lungs in response to chronic hypoxia.…”
Section: Resultsmentioning
confidence: 52%
“…COX-1 is ubiquitously expressed in lung tissue, while COX-2 can be induced in the smooth muscle layer of pulmonary blood vessels by chronic hypoxia (4,5). Disruption or knockdown of COX-2 exacerbates hypoxia-and monocrotaline-induced (MCT-induced) pulmonary hypertension and enhances the contractility of VSMCs (6,7).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, inhibition of COX-2 by celecoxib exhibited beneficial effects against the development of monocrotaline-induced PAH (Rakotoniaina et al, 2008). In contrast, hypoxia-induced PAH was exacerbated by the celecoxib derivative 4-[5-(4-chlorophenyl)-3-(trifluoromethyl)-1H-pyrazol-1-yl] benzenesulfonamide (SC236) (Pidgeon et al, 2004) and in COX-2 knockout animals (Cathcart et al, 2008;Fredenburgh et al, 2008). Herein, we found that acute inhibition of COX-2 can prevent the hypercontractile response to 5-HT in diabetic rats as previously found in PAH induced by intermittent hypoxia (Thomas and Wanstall, 2003) or high pulmonary blood flow (Sato et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…It was demonstrated that COX-2 dependant PGI 2 formation limits the pulmonary hypertensive response to hypoxia in-vivo, partly through attenuation of TXA 2 -dependant platelet activation and deposition. These observations were later confirmed in a COX-gene disrupted mouse model of pulmonary hypertension [28]. This model Immunohistochemical examination of expression profiles of the COX enzymes and downstream enzymes of COX metabolism in lung cancer showed that COX-2 and TXS expression was abundant in lung cancer, but that PGIS expression was absent [30].…”
mentioning
confidence: 91%